1980
DOI: 10.1002/1097-4679(198010)36:4<932::aid-jclp2270360417>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' MMPI performance, cynicism, estrangement, and personal adjustment as a function of race and sex

Abstract: Investigated race and sex differences of lower-class adolescents ( N = 76) on the MMPI, cynicism, estran ement, and ACL ersonal adjustment scales. Results revealed no racial diieerences on MMPfclinical scales or the ACL personal adjustment scale. Significant racial differences on L, F, and cynicism s~pported the inte retation of cultural differences rather than differential racial adjustment. Fa differences were more prevalent than race difference and discussion cautioned against overlooking sex differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In studies in which matched and unmatched analyses were presented, the matched analyses were included in the current meta-analyses. Studies in which participants were generally identified as similar on a demographic characteristic (e.g., socioeconomic status), but in which the participants were not matched or in which the demographic characteristic was not directly analyzed were not considered to be demographically matched studies (e.g., Moore & Handal, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…In studies in which matched and unmatched analyses were presented, the matched analyses were included in the current meta-analyses. Studies in which participants were generally identified as similar on a demographic characteristic (e.g., socioeconomic status), but in which the participants were not matched or in which the demographic characteristic was not directly analyzed were not considered to be demographically matched studies (e.g., Moore & Handal, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Cynicism has been conceptualized as a domain-specific construct and has been studied in different contexts. For example, literature is replete with concepts such as trait cynicism (Moore and Handal, 1980;Mirvis and Kanter, 1991), police cynicism (Regoli et al, 1989), political cynicism (Perloff and Kinsey, 1992), legal cynicism (Sampson and Bartusch, 1998), press cynicism (Schudson, 1999), organizational cynicism (Andersson, 1996;Andersson and Bateman, 1997;Dean et al, 1998;Abraham, 2000), etc. Consumer cynicism too is proposed to be domain-specific (Chylinski and Chu, 2010;Helm et al, 2015).…”
Section: Cynicismmentioning
confidence: 99%
“…(4) individuals who lack literacy and affluence develop cynicism (Mirvis & Kanter, 1991). The role of a person's demographics on cynicism was also established by researchers like Moore and Handal (1980), Andersson (1996), Sridharan and Viswanathan (2008), and Chikweche and Fletcher (2010). We propose that these demographic variables will also be significant in the consumption domain.…”
Section: Proposed Outcomes Of Consumer Cynicismmentioning
confidence: 82%
“…The results showed that (1) people younger and older than middle‐aged persons are more cynical, (2) males tend to be more cynical than females, (3) minority races are more cynical than Whites, and (4) individuals who lack literacy and affluence develop cynicism (Mirvis & Kanter, 1991). The role of a person's demographics on cynicism was also established by researchers like Moore and Handal (1980), Andersson (1996), Sridharan and Viswanathan (2008), and Chikweche and Fletcher (2010). We propose that these demographic variables will also be significant in the consumption domain.…”
Section: Future Research Directions Based On Ado‐tcm Frameworkmentioning
confidence: 89%
See 1 more Smart Citation